2020
DOI: 10.1038/s41598-020-78687-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of heart rate responses and the anti-G straining manoeuvre effectiveness on G tolerance in a human centrifuge

Abstract: Increased heart rate (HR) is a reaction to head-to-toe gravito-inertial (G) force. The anti-G straining manoeuvre (AGSM) is the crucial technique for withstanding a high-G load. Previous studies reported the main effects of HR only or AGSM only on G tolerance. We assessed the combined effect of HR and AGSM on the outcome of 9G profile exposure. A total of 530 attempts for the 9G profile were extracted to clarify the association of interest. Subjects with an AGSM effectiveness of less than 2.5G had a 2.14-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…After adjustment for confounders, we also identified that participants with higher WCFI had higher G tolerance during training, especially for SGT. In addition, AGSM effectiveness is one of the determinants of SGT; moreover, it compensates for the weaker cardiovascular responses against GLOC [11]. Therefore, compared to RGT, we found that the WCFI had a stronger correlation with the SGT value.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…After adjustment for confounders, we also identified that participants with higher WCFI had higher G tolerance during training, especially for SGT. In addition, AGSM effectiveness is one of the determinants of SGT; moreover, it compensates for the weaker cardiovascular responses against GLOC [11]. Therefore, compared to RGT, we found that the WCFI had a stronger correlation with the SGT value.…”
Section: Discussionmentioning
confidence: 66%
“…From the literature review, we also summarized that weight is positively correlated with G tolerance [10,20]. In addition, our former findings identified that there is an inverse relationship between the G tolerance and HR on the ground [10,11]. As stated above, we therefore presumed that CFI might also be connected to G tolerance during the centrifuge training.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations